Air born dust particles effects on microwave propagation in arid-area - Elsheikh, Elfatih A. A.; Suliman, F.M.; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Ismail, Ahmad Fadzil; Elshaikh, Z. E. O.; Chebil, Jalel (IEEE, 2018)
Dust storms can degrade visibility and increase atmospheric attenuation. Therefore, microwave (MW) propagation is severely affected by dust storms in many parts of the world. Air-born dust particles may affect electromagnetic waves during a dust storm. In this paper air- born dust particles effects are studied based on measured visibility. Recent analytical and numerical models results are compared to the measured at 14 GHz. Consequently, measured attenuation is significantly greater than the predicted using recent analytical and numerical models. Dust storms can degrade visibility and increase atmospheric attenuation. Therefore, microwave (MW) propagation is severely affected by dust storms in many parts of the world. Air-born dust particles may affect electromagnetic waves during a dust storm. In this paper air- born dust particles effects are studied based on measured visibility. Recent analytical and numerical models results are compared to the measured at 14 GHz. Consequently, measured attenuation is significantly greater than the predicted using recent analytical and numerical models.